2013
DOI: 10.1345/aph.1r736
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Evaluation of a Large Niacin Therapeutic Interchange Program

Abstract: Data from a medication use evaluation of modified-release niacin products therapeutic interchange in a large US Department of Veterans Affairs health care facility show that the switch from Niaspan to Slo-Niacin had no negative effects on lipid-altering efficacy or safety but generated significant cost avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Veterans who were on Niaspan (5321 subjects) were switched to Slo-Niacin and followed for 2 years. The results showed comparable safety/side effects and lipid benefits and Slo-Niacin had even greater lowering of TG [39]. A third NA product that uses a wax-matrix for its extended-release formulation is Endur-Acin (Endurance Products Inc).…”
Section: Choosing An Na Formulationmentioning
confidence: 99%
“…Veterans who were on Niaspan (5321 subjects) were switched to Slo-Niacin and followed for 2 years. The results showed comparable safety/side effects and lipid benefits and Slo-Niacin had even greater lowering of TG [39]. A third NA product that uses a wax-matrix for its extended-release formulation is Endur-Acin (Endurance Products Inc).…”
Section: Choosing An Na Formulationmentioning
confidence: 99%
“…However, this treatment was accompanied by unwanted side effects (reviewed in [5]), most prominently prostaglandin-dependent vasodilation in the skin (flushing) [6] and hepatotoxicity [7] (for review, see [8]), with the latter becoming negligible by applying niacin in a different formulation [9] (reviewed in [10]). Nevertheless, high niacin dosing can result in discomforting flushes [11], but niacin is still in use [12,13] and also marketed as a food supplement. Several studies showed protective effects of high NAD + levels in model systems as well as in humans under certain pathological conditions or in the context of the aging process, possibly due to preserving energy production in mitochondria [14][15][16][17][18][19][20].…”
Section: Nad + Supplementationmentioning
confidence: 99%